A regional climate palaeosimulation for Europe in the period 1500–1990 – Part 1: Model validation - J. J. Gómez-Navarro; J. P. Montávez; S. Wagner; E. Zorita (Climate of the Past, 2013)
We present and analyse a high-resolution regional climate palaeosimulation encompassing the European region for the period 1500–1990. We use the regional model MM5 driven at the boundaries by the global model ECHO-G. Both models are forced by reconstructions of three external factors: greenhouse gas concentrations, total solar irradiance and volcanic activity. The simulation skill is assessed in a recent period by comparing the model results with the Climate Research Unit (CRU) database. The results show that although the regional model is tightly driven by the boundary conditions, it is able to improve the reliability of the simulations, narrowing the differences to the observations, especially in areas of complex topography. Additionally, the evolution of the spatial distributions of temperature and precipitation through the last five centuries is analysed, showing that the mean values of temperature reflects the influence of the external forcings. However, contrary to the results obtained under climate change scenario conditions, higher-order momenta of seasonal temperature and precipitation are hardly affected by changes in the external forcings.